2014
DOI: 10.1159/000360271
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Catheter-Related Bacteremia with Taurolidine-Citrate Catheter Locks: A Systematic Review and Meta-Analysis

Abstract: Background: Preliminary evidence from some studies suggests that taurolidine-citrate locks decrease catheter-related bacteremia (CRB), which is a major cause of morbidity and mortality in patients using intravascular catheters. No previous study has sought to summarize existing evidence on the use of taurolidine-citrate locks. A systematic review and meta-analysis were undertaken to determine whether taurolidine-citrate was more effective than heparin in the prevention of CRB. Methods: The major English (PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 72 publications
2
48
1
1
Order By: Relevance
“…In contrast with previous results presented by Liu et al (2014) and Solomon et al (2010), this study detected the presence of similar mechanical complications between the groups, after the exclusion of AVF as a cause for removal. Winnicki et al (2018) reported the results of a randomized multicenter study that evaluated the role of prophylactic therapy using two different treatments: taurolidine-citrate-heparin twice a week and 4% citrate three times a week.…”
Section: Abdulcontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast with previous results presented by Liu et al (2014) and Solomon et al (2010), this study detected the presence of similar mechanical complications between the groups, after the exclusion of AVF as a cause for removal. Winnicki et al (2018) reported the results of a randomized multicenter study that evaluated the role of prophylactic therapy using two different treatments: taurolidine-citrate-heparin twice a week and 4% citrate three times a week.…”
Section: Abdulcontrasting
confidence: 99%
“…In recent decades, meta-analyses and systematic reviews have shown the benefits of prophylactic lock therapy compared to heparin for reducing the incidence of CR-BSI in HD patients (Labriola et al, 2008;Jaffer et al, 2008;Yahav et al, 2008;Rabindranath et al, 2009;Snaterse et al, 2011;Zhao et al, 2014;Liu et al, 2013;Liu et al, 2014;Wang et al, 2016;Zang et al, 2017;Zcharioudakis et al, 2014). The ideal solution for locking prophylactic therapy, as well as its longterm adverse effects, is yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to prior studies indicating that the use of Taurolock was associated with a higher rate of catheter exchange, our data revealed that catheter exchange was required less frequently during period two than during period one, with 14 exchanges per 100 patient-years during period two and 45 exchanges per 100 patient-years during period one (P = 0.05). Therefore, the greatest benefit of Taurolock may be a reduction in the rate of dialysis catheter exchange [17] [18].…”
Section: Discussionmentioning
confidence: 99%
“…Taurolidine is an effective antibacterial substance [1][2][3][4][5][6][7][8] utilized to counteract catheterrelated infections [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The substance is further effective against malignancy both, in vivo and in vitro [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%